Perceived discrimination and antisocial behaviour among Chinese rural‐to‐urban migrant adolescents: Mediating effects of social support. (11th May 2016) - Jia, Xuji; Liu, Xia
Abstract : Using cross‐sectional data from rural‐to‐urban migrant adolescents in urban areas of Beijing, China, we examined the mediating effects of social support (i.e. teacher support and classmate support) in the relationship between perceived discrimination (PD) and antisocial behaviour (ASB) among Chinese migrant adolescents. Participants were 897 adolescents (459 boys and 438 girls, mean age = 13.34 years) from four migrant schools (68.8%) and four public schools (31.2%). Participants completed self‐report questionnaires concerning PD, ASB, teacher support and classmate support. Results indicated that Chinese migrant adolescents who perceived more discrimination were more likely to engage in ASB. Teacher support partially mediated the relationship between PD and ASB. Gender moderated this mediational relationship, such that teacher support exerted a mediating role among girls, but not boys. The findings suggest that reductions in teacher support may partially account for the effect of PD on ASB among Chinese migrant adolescents girls.